Sleep disorders in pregnancy and postpartum - Markovic, Milos; Gojković, Marjana; Mušić, Demir (Engrami, 2026)
Sleep disorders are highly prevalent during pregnancy and the postpartum period and arise as a consequence of complex hormonal, anatomical, neurobiological, and psychosocial changes. Among primary sleep disorders, insomnia, obstructive sleep apnea, restless legs syndrome, and parasomnias are most commonly present in the perinatal period, and these conditions are associated with significant adverse maternal and fetal outcomes. The relationship between sleep and perinatal psychiatric disorders is often bidirectional: sleep disturbances may represent an early symptom, a risk factor, and a pathophysiological driver of depression, anxiety disorders, bipolar disorder, and postpartum psychosis, as well as other primary psychotic disorders. This paper reviews clinically relevant primary sleep disorders, the principles of their treatment, and the management of sleep disturbances occurring within other psychiatric disorders during the perinatal period.
Keywords: pregnancy; breastfeeding; perinatal period; sleep disorders; treatment